Maternal Diet and Infant Feeding Practices Are Associated with Variation in the Human Milk Microbiota at 3 Months Postpartum in a Cohort of Women with High Rates of Gestational Glucose Intolerance. Issue 2 (4th September 2020) - LeMay-Nedjelski, Lauren; Asbury, Michelle R; Butcher, James; Ley, Sylvia H; Hanley, Anthony J; Kiss, Alex; Unger, Sharon; Copeland, Julia K; Wang, Pauline W; Stintzi, Alain; O'Connor, Deborah L
ABSTRACT: Background: Human milk contains a diverse community of bacteria believed to play a role in breast health and inoculation of the infant's gastrointestinal tract. The role of maternal nutrition and infant feeding practices on the human milk microbiota remains poorly understood. Objective: Our aim was to explore the associations between maternal diet (delivery to 3 mo postpartum), infant feeding practices, and the microbial composition and predicted function in milk from women with varied metabolic status. Methods: This was an exploratory analysis of a previously completed prospective cohort study of women with varying degrees of gestational glucose intolerance (NCT01405547). Milk samples ( n = 93 mothers) were collected at 3 mo postpartum. Maternal dietary information (validated food-frequency questionnaire) and infant feeding practices (human milk exclusivity, frequency of direct breastfeeding per day) were collected. V4-16S ribosomal RNA gene sequencing (Illumina MiSeq) was conducted to determine microbiota composition. Results: Intake of polyunsaturated fat [β estimate (SE): 0.036 (0.018), P = 0.047] and fiber from grains [0.027 (0.013), P = 0.048] were positively associated with ɑ-diversity (Shannon index) of human milk. Overall microbial composition of human milk clustered based on human milk exclusivity (weighted UniFrac R 2 = 0.034, P = 0.015; Bray-Curtis R 2 = 0.041, P = 0.007), frequency of direct breastfeeding per day (Bray-Curtis R 2 = 0.057, P = 0.026), and maternal fiber intake from grains (Bray-Curtis R 2 = 0.055, P = 0.040). Total fiber, fiber from grains, dietary fat, and infant feeding practices were also associated with a number of differentially abundant taxa. The overall composition of predicted microbial functions was associated with total fiber consumption (Bray-Curtis R 2 = 0.067, P = 0.036) and human milk exclusivity (Bray-Curtis R 2 = 0.041, P = 0.013). Conclusions: Maternal consumption of fiber and fat, as well as mother's infant feeding practices, are important determinants of the human milk microbiota. Understanding whether these microbial changes impact an infant's overall health and development requires future study.